2016
DOI: 10.1080/19420862.2016.1267088
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing assembly and production of native bispecific antibodies by codon de-optimization

Abstract: When production of bispecific antibodies requires the co-expression and assembly of three or four polypeptide chains, low expression of one chain can significantly limit assembly and yield. kλ bodies, fully human bispecific antibodies with native IgG structure, are composed of a common heavy chain and two different light chains, one kappa and one lambda. No engineering is applied to force pairing of the chains, thus both monospecific and bispecific antibodies are secreted in the supernatant. In this context, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…We have shown in our previous study that the effects on light chain content and IgG form distribution obtained with different de-optimized variants were consistent between transient transfections using PEAK cells and expression from stable CHO pools [13]. In this study, the results obtained with both systems were also similar for K2O41 but appeared to be different for K2O30.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…We have shown in our previous study that the effects on light chain content and IgG form distribution obtained with different de-optimized variants were consistent between transient transfections using PEAK cells and expression from stable CHO pools [13]. In this study, the results obtained with both systems were also similar for K2O41 but appeared to be different for K2O30.…”
Section: Discussionsupporting
confidence: 76%
“…We selected these three κλ bodies as they displayed different degrees of lambda chain overexpression and we aimed at restoring a more balanced expression via a codon de-optimization approach [13]. However, to avoid designing several new sequences for each candidate as previously described, we evaluated the possibility to achieve down modulation while restricting the sequence modification to the constant region of the lambda chain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Columns specific for kappa- and lambda-monospecific antibodies isolation were then adopted followed by Protein A purification, although only around 50% of the final product is κλ body with the rest mainly including kappa-kappa and lambda-lambda antibody side products [140,164]. Interestingly, another research group reported that codon de-optimization of the lambda chain sequence increased the κλ body yield two-fold and enhanced the relative distribution of bispecific antibodies in a low kappa chain expressing κλ body cell line [165].…”
Section: Strategies To Improve Bispecific Antibody Production and mentioning
confidence: 99%